The increasing physical inactivity of teenagers aged 12-16 years old of Saint Joseph College - Louie Petere Gula; Kevin Sumayang (MEDIKORA, 2022)
This study aims to identify the following factors that affect the physical inactivity of the students in saint joseph college aged 12- 16 years old. It aims to understand the impact of this crisis and how to address this pressing issue. A descriptive- survey research design was utilized to document the respondents' behavior, demographics, and experiences correlated to the questions provided. The questionnaire includes 15-item questions that seek to gather information on their basic profile, current experiences, and behavior towards physical activities. The study discovers that teenagers aged 12-16 years old are inactive in physical activities and sports due to some reasons like exposure to too much time to gadgets, whether the activity provides a fun and offers socialization, lack of motivation, occupied schedules for other matters, the covid-19 pandemic, costly sports equipment on the sports of their interest, the unavailability of playing area, and lastly health concerns. Therefore, physical inactivity only alleviates certain issues, physically, mentally, spiritually, and socially. Physical inactivity is the result of demotivated individuals, physical illiteracy, prolonged screen time, and health issues.